ANALYSIS OF FRACTURE ENERGY IN DOUBLE CANTILEVER BEAM SIMULATION USING COHESIVE ZONE MODEL AND VIRTUAL CRACK CLOSURE TECHNIQUE - Widanto, Muhammad Hadi; Wulandari, Rini; Fairuza , Syarifah (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
Composite materials are vital in aerospace and other fields due to their high load-bearing capacity and lightweight nature. However, they are prone to failure, particularly delamination, which results from high interlaminar stresses and stress concentrations. This study investigates delamination through simulations of Double Cantilever Beam (DCB) tests using various finite element methods (FEM) for fiber directions 1 and 2. GIc values from previous experiments, 0.5 N/mm for fiber direction 1 and 0.3 N/mm for fiber direction 2, were employed in the simulations. The critical force values obtained for fiber direction 1 using the cohesive contact CZM method, cohesive elements, and VCCT were 30.55 N, 30.33 N, and 30.08 N, respectively. For fiber direction 2, the values were 33.98 N, 33.38 N, and 29.94 N. Comparisons were made between two-dimensional and three-dimensional models and experimental results. The two-dimensional model exhibited an error of -1.16%, whereas the three-dimensional model showed an error of 5.10%. For fiber direction 2, errors were -1.83% and 0.85%, respectively. Positive errors indicate higher simulation results compared to experimental data, while negative errors reflect lower simulation results.